Faktor Risiko Kejadian TB Paru di Desa Gunturu Kecamatan Herlang Kabupaten Bulukumba - Wijaya, Dian Rezki; Nurdiyanah, Nurdiyanah; Ibrahim, Irviani Anwar; Amansyah, Munawir; Ekasari, Ranti (HIGIENE: Jurnal Kesehatan Lingkungan, 2020)
Tuberculosis (TB) is a disease caused by mycobacterium tuberculosis with a high transmission rate. It attacks lung (80%), while the remaining attack the organs outside the lungs. In Indonesia, it was estimated around 1 million new TB cases with 110,000 deaths each year. In 2018, Bulukumba Regency was in third highest number of TB suspects in South Sulawesi. This study aimed to determine the risk factors for pulmonary tuberculosis in Gunturu Village. This research was a quantitative study with a prevalence study design. All residents of Gunturu Village became a population while the sample was obtained by purposive sampling with 102 people. The data was collected by interview, observation, and measurement. Risk factors for pulmonary tuberculosis in Gunturu Village were nutritional status (p = 0.0575, OR = 1.267) and education level (p = 0.871, OR = 1.083). While smoking status (p = 0.255, OR = 0.553), work status (p = 0.369, OR = 0.660), ventilation (p = 1,000, OR = 1,000) and lighting (p = 0.602, OR = 0.646) were not risk factors. Active case finding needs to be improved by carrying out household contact investigations and screening in at-risk populations as well as improving the recording of TB reports. Keywords : Pulmonary Tuberculosis, Risk Factor